Understand Shakespeare Shakespearean tragedy (Victoria : Learning Essentials, 2000)
Summary: Offers some answers by focusing on two of Shakespeare's best-known plays,'Hamlet' and'McBeth'. It examines the degree to which the hero is responsible for his own fate, and scrutinises his responses to social, political and personal pressures.
Presenter: Alan Dilnot, Sue Fweng
Keywords: English literature; Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Tragedies